Microstructure evolution, formation of Ti3Ni4 nanoparticles and nanotwins (0 0 1)B19′ and interrelation with mechanical properties in the Ti-50.7 at. % Ni alloy during multiple martensitic transformations and subsequent aging. (2021) - Churakova, Anna; Kayumova, Elina; Tolstov, Nikita
Abstract: In this paper, we investigated the microstructure of the Ti-50.7 at.% Ni alloy after multiple martensitic transformations and subsequent aging at a temperature of 400 °C in different states. We studied the features of the formation of Ti3Ni4 nanoparticles and nanotwins I type depending on the initial microstructure in the Ti-50.7 at.% Ni alloy. It was shown that in the structure with a higher dislocation density the formation of nanotwins of type I took place during subsequent aging. As well as the relationship of microstructural changes and mechanical characteristics.